A prospective study on cardiac changes (electrocardiographic, enzymatic and echocardiographic) in birth asphyxiated neonates admitted in tertiary care centre - Shadique, A. Muhammed; Sailavasan, Madhivanan (International Journal of Contemporary Pediatrics, 2019)
Background: Reduced myocardial performance and cardiac output following perinatal asphyxia may significantly complicate perinatal management and may contribute to increased end-organ damage and mortality. Hence the present study was done with the aim to assess the usefulness of echocardiography, electrocardiography (ECG), and cardiac enzymes in evaluating myocardial damage in perinatal asphyxia neonates and to assess their correlation with different stages of hypoxic-ischemic encephalopathy (HIE) and outcome. Methods: The study was conducted in the NICU, Department of Pediatrics, Government Chengalpattu Medical college hospital between August 2017 and August 2018 using 70 birth asphyxiated term babies. The asphyxiated babies were resuscitated as per NRP guidelines and were stratified into HIE stages as per Levene system of classification and were managed as per clinical condition. ECG grading, echo changes were noted. Creatinine kinase-MB (CKMB) levels were measured and documented after 12 hours of life among these babies and were analysed. Results: Of 70 cases, 36 (51.4%) had mild, 26 (37.1%) moderate and 8 (11.4%) severe HIE. Abnormal ECG was observed in 63 cases. Raised CKMB levels were found in 67 (95.7%) and abnormal echo findings were noted in 46 (65.7%) babies. ECG, echo changes and CKMB levels showed increasing abnormalities with increasing severity of HIE (p=0.000, 0.030 and 0.001 respectively). 8 babies in present study expired. Conclusions: Cardiac abnormalities among asphyxiated neonates requires high index of suspicion. ECG abnormalities, echo changes, elevated CK-MB levels in babies with HIE can help us identify neonates at risk of complications and guide in timely intervention that can prevent mortality of these babies and help us achieve better neurological outcome in these babies.